Advantages of Micropulse Technology as a Method of Choice for the Treatment of Secondary Glaucoma in Patients with Corneal Diseases - A. V. Sidorova; A. V. Starostina; M. A. Pecherskaia; K. A. Stefankova (Oftalʹmologiâ)
Postkeratoplasty glaucoma develops after cornea transplantation in 10–53 % cases. For ophthalmotonus stabilization in patients, it was proposed to use micropulse laser surgery.Purpose. To evaluate the effectiveness of micropulse laser surgery in patients with secondary refractory glaucoma after keratoplasty.Patients and methods. The study included 27 eyes after different types of keratoplasty. The average level of intraocular pressure was 33.2 ± 3.7 mmHg, the average number of hypotensive drops was 2.9 ± 0.7. Visual acuity varied from incorrect light perception to 0.3 with correction. Micropulse laser treatment was performed with the standard settings and a power of 2800 mW.Results. On the first day after laser surgery, 24 patients had a decrease in IOP by an average of 24 % to 25.6 ± 3.3 mmHg. Three patients had a reactive increase in IOP by an average of 5 % to 33–36 mmHg. After 12 months of follow-up, the average IOP level was 24.9 ± 1.8 on the hypotensive drops, a decrease of IOP was 24.5 %, the number of hypotensive drops was reduced to 2.1 ± 0.7. In 6 cases, an increase in visual acuity by 1–2 lines was diagnosed due to a decrease in corneal edema. In 3 cases, 1–2 months after laser surgery, patients underwent second transplantation of the Descemet membrane. However, in 2 patients, an IOP increased again to 27–30 mmHg, and it was decided to conduct a repeated micropulse surgery with a power of 2800 mW. When observed for up to 3 months, IOP respond to the target level and averaged 18-20 mmHg. Using ultrasound biomicroscopy, the dynamics of changes in the thickness of the ciliary body was followed in all patients, the average thickness before surgery was 0.56 ± 0.11 mm. After 12 months, there was no statistical difference with the preoperative thickness, the average values were 0.55 ± 0.10 mm, the safety of its main structures was noted.Conclusion. Micropulse cyclophotocoagulation is an effective and safe method of treating secondary refractory glaucoma in the eyes both before keratoplasty and after repeated cornea transplantation, which opens up new prospects in the treatment of glaucoma combined with corneal diseases.